Frailty-related factors and 1-year renal function change after sodium-glucose cotransporter-2 inhibitors in elderly chronic kidney disease patients - Hye-Mi Noh; Sei Hong Min; Hyung-Seok Lee; Sung Gyun Kim; Jun Goo Kang; Jwa-Kyung Kim (Kidney Research and Clinical Practice, 2025)
Background Sodium-glucose cotransporter-2 inhibitors (SGLT2i) are first-line therapy for chronic kidney disease (CKD). However, evidence regarding their safety and efficacy in frail elderly patients remains limited. This study evaluated the impact of frailty-related factors on renal outcomes in elderly CKD patients treated with SGLT2i. Methods We retrospectively analyzed 302 elderly CKD patients (≥65 years) newly prescribed SGLT2i. Four frailty-related factors included advanced age (≥75 years), anemia, low Geriatric Nutritional Risk Index (GNRI ≤98), and proteinuria. Rapid renal decline was defined as an absolute decrease in estimated glomerular filtration rate (eGFR) >10 mL/min/1.73 m² within 12 months or a ≥40% reduction from baseline. Results The mean age was 75.7 ± 8.1 years, and baseline eGFR was 48.1 mL/min/1.73 m². Anemia was present in 49.3% and low GNRI in 12.3% of patients. Those with low GNRI were older, had lower BMI and serum albumin levels, higher prevalence of anemia and proteinuria, and greater 12 month decline in eGFR (-4.0 vs. -2.0 ml/min/1.73m2/year, p < 0.01). Rapid renal decline occurred in 29 patients (9.6%), and risk increased with accumulation of frailty factors. Advanced age (≥75 years) alone was associated with higher risk (OR 2.33; 95% CI 1.03-5.32), which further increased when combined with anemia and proteinuria (OR 4.85; 95% CI 2.19-10.77). Patients with all four components had the highest risk (OR 9.70; 95% CI 3.82-24.81). Conclusion While SGLT2i are generally effective in elderly CKD patients, those with frailty-related factors, particularly malnutrition, proteinuria, and anemia, appear to be at higher risk of rapid decline in renal function. These patients may benefit from more individualized risk assessment and management.